ISOLATION AND SCREENING OF SALT TOLERANT AND PLANT GROWTH PROMOTING PROPERTIES OF BACTERIA FROM SALINE SOIL - Ibrahim, Muhammad; Kawo, A. H.; Yahaya, S.; Aminu, B. M.; Shuaibu, H. K. (FUDMA Journal of Sciences, 2025)
Soil salinity is a limiting factor of agricultural production in arid and semi-arid areas that reduces yields and optimal crop production. This study aim of this work has to do with assessing the effect of bacteria isolated from the saline soil. The soil sample used for the research were sampled at DAMBATTA and KURA of Kano State using a randomized sampling method. The physicochemical properties and microbiological characteristics were determined using standard methods. The pH of DAMBATTA and KURA were (8.63 and 9.48) respectively, and were all weakly alkaline organic matter, phosphorus, and nitrogen, were all higher in Kura. The moisture content was higher in Kura (0.85%). Three (3) gram positive and four (4) gram negative bacteria isolates were isolated, seven (7) isolates that have high potential were identified as Bacillus thuringiensis (DBT 1), Sphingobacterium spp (DBT 2), Myroides spp (DBT 3), Bacillus subtilis (KK1), Sphingobacterium psychroaquaticum (KK5), Bacillus cereus (KK8), Paenochrobactrum glaciei (K4). The optimum salt tolerance showed that DBT 3 has the highest tolerance of 10 % whereas DBT2 recorded the least at 0.6% while isolates from Kura, KK1 has the highest salt tolerance of 5% and the least was recorded By K4 having 0.4%. For growth promoting properties, DBT3 and KK5 have the highest N-fixation rate, and the highest IAA was recorded in DBT1 and KK8. For P-solubilization potential, DBT3 and KK1 were highest. This study showed variation in bacterial isolates to salt concentration and their capacity to produce growth promotion properties.
Keywords: PGPR; Salt Tolerance; P-Solubilization; N-Fixation